2014
DOI: 10.1021/es501067w
|View full text |Cite
|
Sign up to set email alerts
|

Multinuclear Complex Formation between Ca(II) and Gluconate Ions in Hyperalkaline Solutions

Abstract: Alkaline solutions containing polyhydroxy carboxylates and Ca(II) are typical in cementitious radioactive waste repositories. Gluconate (Gluc(-)) is a structural and functional representative of these sugar carboxylates. In the current study, the structure and equilibria of complexes forming in such strongly alkaline solutions containing Ca(2+) and gluconate have been studied. It was found that Gluc(-) significantly increases the solubility of portlandite (Ca(OH)2(s)) under these conditions and Ca(2+) complexe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
76
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(91 citation statements)
references
References 48 publications
11
76
3
Order By: Relevance
“…Concerning Gluc -, a surprisingly high log Ka, -11.18 was determined (T = 37 °C, I = 0.15 M) employing glass electrode [24]. Using hydrogen electrode, values of -13.66 [61] and -13.68 [62] were deduced (T = 25 °C, I = 1 M), whilst -13 was proposed on the basis of 13 C NMR experiments (T = 22 °C, I = 0.1 M) [36]. Interestingly, it was found that gluconate ion could be deprotonated twofold; the log Ka of GlucH-1 2was found to be -14.02 [61].…”
Section: Deprotonation Of Hydroxycarboxylates In Strongly Alkaline Mementioning
confidence: 99%
See 4 more Smart Citations
“…Concerning Gluc -, a surprisingly high log Ka, -11.18 was determined (T = 37 °C, I = 0.15 M) employing glass electrode [24]. Using hydrogen electrode, values of -13.66 [61] and -13.68 [62] were deduced (T = 25 °C, I = 1 M), whilst -13 was proposed on the basis of 13 C NMR experiments (T = 22 °C, I = 0.1 M) [36]. Interestingly, it was found that gluconate ion could be deprotonated twofold; the log Ka of GlucH-1 2was found to be -14.02 [61].…”
Section: Deprotonation Of Hydroxycarboxylates In Strongly Alkaline Mementioning
confidence: 99%
“…For the most frequently studied Gluc - (Figure 7), the thermodynamic association constant, log β11 0 , was found to be 1.7-1.9 [37,[84][85][86]. At varying ionic strength, log β11 varies in the range of 0.37-1.36 obtained from Ca-ISE potentiometric [22,62,75,[87][88][89][90], solubility [82], ion-exchange [91] and 13 C NMR spectroscopic [37] measurements. The value of 0.37 [62] is probably underestimated, since it was obtained indirectly from pH-potentiometric titrations performed in alkaline solutions.…”
Section: Ca 2+ -Complexes Of Sugar Carboxylates Forming In Neutral Mementioning
confidence: 99%
See 3 more Smart Citations